Glans Ischemia after Circumcision in a 16-Year-Old Boy: Full Recovery after Angiography with Local Spasmolysis, Systemic Vasodilatation, and Anticoagulation - Richard Gnatzy; Jochen Fuchs; Manuela Siekmeyer; Anne Bettina Beeskow; Jan-Hendrik Gosemann; Martin Lacher (European Journal of Pediatric Surgery Reports, 2018)
Circumcision is one of the most frequent procedures performed by pediatric surgeons. A dorsal penile nerve block (DPNB) is commonly used for perioperative analgesia. We report the case of a 16-year-old boy with ischemia of the glans who presented on the first postoperative day after circumcision under DPNB (0.25% bupivacaine) at an outside hospital. The patient underwent immediate angiography under sedation. An intra-arterial spasmolysis was performed with alprostadil and nitroglycerine and a sufficient perfusion of the glans penis was confirmed. Subsequently, systemic sildenafil, arginine, and heparin were given. Following this 3-day medical treatment, ischemia resolved completely. Our case emphasizes the role of invasive angiography in the diagnostic workup and the therapeutic possibilities of local spasmolysis, systemic vasodilatation, and anticoagulation.